2020
DOI: 10.1101/2020.06.18.20134759
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic diversity among SARS-CoV2 strains in South America may impact performance of Molecular detection

Abstract: Since its emergence in Wuhan (China) on December 2019 the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has rapidly spread worldwide. After its arrival in South America in February 2020 the virus has expanded throughout the region infecting over 900,000 individuals with approximately 41,000 reported deaths to date. In response to the rapidly growing number of cases, a number of different primer-probe sets have been developed. However, despite being highly specific most of these primer-probe sets… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
1
20
0
2
Order By: Relevance
“…Samples were taken from ambulatory patients in the respiratory triage of the Tlaltenango health center in Cuernavaca, Morelos, Mexico. The RT-qPCR Berlin protocol was used to detect SARS-CoV-2, using only the primers and probe for gene E, since previous studies have shown a weak detection of viral RNA when the RNA-dependent RNA polymerase (RdRp) gene is probed (9,10). As an internal control of RNA content in the samples, the RNase P gene was detected.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were taken from ambulatory patients in the respiratory triage of the Tlaltenango health center in Cuernavaca, Morelos, Mexico. The RT-qPCR Berlin protocol was used to detect SARS-CoV-2, using only the primers and probe for gene E, since previous studies have shown a weak detection of viral RNA when the RNA-dependent RNA polymerase (RdRp) gene is probed (9,10). As an internal control of RNA content in the samples, the RNase P gene was detected.…”
Section: Resultsmentioning
confidence: 99%
“…Samples were taken from ambulatory patients in the respiratory triage of the Tlaltenango health center, in Cuernavaca, Morelos. The RT-qPCR Berlin protocol was used to detect SARS-CoV-2, using only the primers and probe for gene E, since previous studies have shown a weak detection of viral RNA when the RdRp gene is probed [10][11]. As an internal control of RNA content in the samples, the RNase P gene was detected.…”
Section: Resultsmentioning
confidence: 99%
“…have represented novel insights in case of SARS-CoV-2 experiments by accurately detect and quantify rare viral variants within the species ( Khailany et al, 2020 ; Ellinghaus et al, 2020 ; Aiewsakun et al, 2020 ; Ray et al, 2020a ) ( Table 4 ). In addition to the SNP analysis, the incorporation of haplotype diversity analysis with phylogenetic analysis has been frequently used in the SARS-CoV-2 research analyses to study the evolution and population demography of SARS-CoV-2 globally ( Ramírez et al, 2020 ; Fang et al, 2020 ). The molecular and evolutionary relationship with other coronavirus species, closely related species identification etc.…”
Section: Genome-wide Association Studymentioning
confidence: 99%
“…in drug discovery and development ( Song et al, 2009 ). Also, the additional benefits like cost-saving, time to market, in-sight knowledge of drug-receptor interaction, speed up in drug discovery and development increases its popularity in scientific researches ( Ramírez et al, 2020 ).…”
Section: Computer Aided Drug Designmentioning
confidence: 99%